Panchayati Raj institutions grey areas galore-need for time-bound tackling. - Joshi, Uma (1995)
"Describing the 73rd Amendment Act as a watershed in decentralised decision-making, the author warns that if PRIs are to be starved of the statutory powers and autonomy, the measure may ultimately prove to be a futile exercise. The grey areas in the matter of financial autonomy must be dealth with and removed to ensure democratic decentralisation in its true sense. In view of the atmosphere of liberalisation, the decentralisation process with long-term strategies for development needs to be integrated much more effectively, opines the author"
Keywords: Decentralization in government - India; India. Constitution - Amendments - 73rd; Panchayat - India